On the critical behaviour of two-dimensional liquid crystals - Fariñas-Sánchez, A.l.; Botet, R.; Berche, B.; Paredes, R. (Condensed Matter Physics, 2010)
The Lebwohl-Lasher (LL) model is the traditional model used to describe the nematic-isotropic transition of real liquid crystals. In this paper, we develop a numerical study of the temperature behaviour and of finite-size scaling of the two-dimensional (2D) LL-model. We discuss two possible scenarios. In the first one, the 2D LL-model presents a phase transition similar to the topological transition appearing in the 2D XY-model. In the second one, the 2D LL-model does not exhibit any critical transition, but its low temperature behaviour is rather characterized by a crossover from a disordered phase to an ordered phase at zero temperature. We realize and discuss various comparisons with the 2D XY-model and the 2D Heisenberg model. Having added finite-size scaling behaviour of the order parameter and conformal mapping of order parameter profile to previous studies, we analyze the critical scaling of the probability distribution function, hyperscaling relations and stiffness order parameter and conclude that the second scenario (no critical transition) is the most plausible. Зазначено, що модель Лебволя - Лашера (Lebwohl - Lasher) (LL) є традиційною моделлю, яка використовується для опису переходу нематик - ізотропна фаза у реальних рідких кристалах. Вивчено температурну поведінку та скінченно-мірний скейлінг двовимірної (2D) LL моделі за допомогою числових методів. Розглянуто два можливих сценарії. В одному з них, 2D LL-модель представляє фазовий перехід, подібний до топологічного переходу, який виникає в 2D XY-моделі. У другому сценарії 2D LL-модель не демонструє жодного критичного переходу, проте її низькотемпературна поведінка характеризується кросовером із невпорядкованоої у впорядковану фазу при нулі температури. Здійснено та обговорено різні порівняння із 2D XY-моделлю і 2D моделлю Гайзенберга. Доповнивши попередній розгляд скінченно-мірною поведінкою профіля параметра порядку і його конформальним відображенням, проаналізовано критичний скейлінг функції розподілу, гіперскейлінгові співвідношення і жорсткість параметра порядку та зроблено висновок про те, що другий сценарій (жодного критичного переходу) є найбільш ймовірним.